Analysis of the use of antidepressants in patients from non-psychiatric departments in general hospital. (November 2022) - Yang, Wei; Wang, Ying; Huang, Shi; Su, Xianming; Jiang, Wenhui; Ren, Yanping
Highlights: A Antidepressant medication in all clinical specialties does not completely conform to the guideline recommendation, and some specialties have not yet formulated relevant guidelines or specifications. B There are also significant differences in drug use among patients with mental disorders with or without a clear diagnosis. C Antidepressants for different states of mental disorders, especially mild and moderate mental disorders, need to be further regulated. Abstract: This study aimed to analyze the use of antidepressants in non-psychiatric departments. The data of patients treated with antidepressants in non-psychiatric departments of the First Affiliated Hospital of Xi 'an Jiaotong University, were collected from 2014 to 2018. The average annual growth rate of antidepressants use was 22.83%. According to the number of patients at discharge, the classification descending order was: SSRIs, Flupenthixol-TCA, SNRIs, TCAs, SARIs, and NaSSA. Sertraline and flupenthixol-melitracen were the main drugs used in SSRIs and Flupenthixol-TCA, respectively. Neurology, Cardiology, and Geriatrics were the main departments prescribing SSRIs, Flupenthixol-TCA and SNRIs. The antidepressants used by all patients were mainly SSRIs according to drug classification, but the specific drug use in unclear diagnosis group was dominated by flupenthixol-melitracen, while it was sertraline in clear diagnosis group. The proportion of Flupenthixol-TCA in anxiety state group was higher than that in depression state group, While the situation in SSRIs is the opposite. More guidelines should be formulated to improve the recognition of comorbidities between specialized diseases and psychiatric disorders. Also, multi-level training should be implemented to perform the standard diagnosis and medication of mental disorders in clinical practice.